Perancangan Alat Pembuatan Briket Batok Kelapa Manual Sebagai Energi Alternatif Ramah Lingkungan - Sakanti, Alya Anindya; Airlangga, Aris Dwi; Chairunnisa, Alivia; Meisyahrani, Helmi; Mujahidin, Rama Husni; Ardiatma, Dodit (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Coconut shell is a biomass waste that is abundantly generated from household activities, traditional markets, and coconut-based food industries. However, its utilization remains limited, and open burning is still commonly practiced, causing environmental pollution and health problems. This study aimed to design and implement a manual coconut shell briquette-making device as an appropriate technology for household and small-scale business applications. The study employed a limited-scale field trial combined with a participatory community approach in Sukasari Village, Serang Baru District, Bekasi Regency. The device consisted of a manual meat grinder, steel frame, PVC pipe, wooden board, and recycled can. Operational testing showed that the device was capable of producing approximately 15–20 kg of briquettes per day. The briquettes exhibited satisfactory physical characteristics, including adequate strength, low smoke emissions, and a burning duration of 45–60 minutes. The implementation received positive responses from the local community and demonstrated potential environmental and economic benefits through biomass waste utilization and alternative energy production.